2016
DOI: 10.1016/j.ymgmr.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The expanding phenotype of MELAS caused by the m.3291T>C mutation in the MT-TL1 gene

Abstract: m.3291T > C mutation in the MT-TL1 gene has been infrequently encountered in association with mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS), however remains poorly characterized from a clinical perspective. In the following report we describe in detail the phenotypic features, long term follow up (> 7 years) and management in a Caucasian family with MELAS due to the m.3291T > C mutation and review the literature on m.3291T > C mutation. The clinical phenotype in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Multiple small hyperintense areas in subcortical white matter of cerebrum on T2 MRI NA NA NA Family of 5 affected individuals in 4 generations Sunami et al [ 10 ] 36 F Photo-induced myoclonus, atrophy of cerebellum, absence of tendon reflexes, truncal ataxia, normal mental status 16% (peripheral leukocytes) NA NA Family of 5 affected individuals in 4 generations Sunami et al [ 10 ] 15 F Generalized seizures, myoclonic jerks, slight cognitive decline, absence of tendon reflexes 27% (peripheral leukocytes) NA NA Family of 5 affected individuals in 4 generations Emmanuele et al [ 13 ] 43 M Progressive myoclonus epilepsy, cerebellar ataxia, cortical and cerebellar atrophy, hearing loss, myopathic weakness, ophthalmoparesis, pigmentary retinopathy, bifascicular heart block, premature graying (20 years) 92% (muscle) Elevated (serum) Normal respiratory chain enzymes. RRFs and succinate dehydrogenase reactive vessels Yarham et al [ 8 ] 51 M Bilateral sensorineural deafness, falls, speech disturbance, weight loss, diabetes mellitus, macroglossia with fatty infiltration, dysarthria, bilateral pes cavus, lipoma, low tendon reflexes, dysmetria, generalized brain atrophy 39% (muscle) Elevated (cerebrospinal fluid) Dystrophic changes and lipid infiltrates, RRFs, COX-negative fibers, succinate dehydrogenase reactive vessels Unaffected sister shows heteroplasmy levels of 6% in both urine and blood Liu et al [ 11 ] 14 F Progressive cerebellar ataxia, frequent myoclonus seizures, recurrent stroke-like episodes, migraine-like headaches with nausea and vomiting, nystagmus, basal ganglia calcification, brain atrophy, and stroke-like lesions 93% (muscle), 67% (blood), 62% (fibroblasts) Elevated (serum) RRF, COX-negative fibers, succinate dehydrogenase reactive vessels Mother of proband (phenotype: emaciation and short stature) and asymptomatic sister of proband have heteroplasmy levels of 46% and 50%, respectively Keilland et al [ 12 ] 15 F Stat...…”
Section: Resultsmentioning
confidence: 99%
“…Multiple small hyperintense areas in subcortical white matter of cerebrum on T2 MRI NA NA NA Family of 5 affected individuals in 4 generations Sunami et al [ 10 ] 36 F Photo-induced myoclonus, atrophy of cerebellum, absence of tendon reflexes, truncal ataxia, normal mental status 16% (peripheral leukocytes) NA NA Family of 5 affected individuals in 4 generations Sunami et al [ 10 ] 15 F Generalized seizures, myoclonic jerks, slight cognitive decline, absence of tendon reflexes 27% (peripheral leukocytes) NA NA Family of 5 affected individuals in 4 generations Emmanuele et al [ 13 ] 43 M Progressive myoclonus epilepsy, cerebellar ataxia, cortical and cerebellar atrophy, hearing loss, myopathic weakness, ophthalmoparesis, pigmentary retinopathy, bifascicular heart block, premature graying (20 years) 92% (muscle) Elevated (serum) Normal respiratory chain enzymes. RRFs and succinate dehydrogenase reactive vessels Yarham et al [ 8 ] 51 M Bilateral sensorineural deafness, falls, speech disturbance, weight loss, diabetes mellitus, macroglossia with fatty infiltration, dysarthria, bilateral pes cavus, lipoma, low tendon reflexes, dysmetria, generalized brain atrophy 39% (muscle) Elevated (cerebrospinal fluid) Dystrophic changes and lipid infiltrates, RRFs, COX-negative fibers, succinate dehydrogenase reactive vessels Unaffected sister shows heteroplasmy levels of 6% in both urine and blood Liu et al [ 11 ] 14 F Progressive cerebellar ataxia, frequent myoclonus seizures, recurrent stroke-like episodes, migraine-like headaches with nausea and vomiting, nystagmus, basal ganglia calcification, brain atrophy, and stroke-like lesions 93% (muscle), 67% (blood), 62% (fibroblasts) Elevated (serum) RRF, COX-negative fibers, succinate dehydrogenase reactive vessels Mother of proband (phenotype: emaciation and short stature) and asymptomatic sister of proband have heteroplasmy levels of 46% and 50%, respectively Keilland et al [ 12 ] 15 F Stat...…”
Section: Resultsmentioning
confidence: 99%
“…Phenotype diversity of Leigh disease has been reported for m.8993T>C mutation in the same MT-ATP6 gene [81]; noticeably, other unusual presentations rather than neurological ones were found with other mitochondrial and nuclear-encoded genes, causing Leigh disease to be ocular and gastrointestinal with MT-ND mutations [82,83], cardiac with NDUF [84,85] and renal with SURF1 and ACAD9 gene defects [86,87]. Previous studies have reported many mitochondrial mutations causing classic MELAS without any detectable phenotypic specificity [88,89]; exceptional renal diseases were detected in association with m.3243 and m.13513G>A as a first manifestation of MELAS [90,91]. Furthermore, MELAS m.3243 was associated with uncommon presentations such as cardiac and ketoacidosis [92,93].…”
Section: Discussionmentioning
confidence: 96%
“…Apparently, the m.3291T > C mutation does not manifest significantly in the heart [1] . Did the propositus undergo comprehensive cardiologic investigations, including echocardiography and long-term ECG-recordings?…”
mentioning
confidence: 88%
“…The patient presented with clinical manifestations of KSS [1] . Which were the clinical manifestations of KSS?…”
mentioning
confidence: 99%